KAJIAN STRUKTURAL DALAM NOVEL BUMI KARYA TERE LIYE - Gek Putu Maysily Jayestha Pureni; Ni Luh Sukanadi; IGA Putu Tuti Indrawati (JIPBSI (Jurnal Ilmiah Pendidikan Bahasa dan Sastra Indonesia), 2023)
This study examines the analysis of novels with a structural approach that aims to (1) analyze the structure in the form of intrinsic elements that build the novel Bumi by Tere Liye and (2) categorize and describe the types of Bumi novels by Tere Liye, which focuses on the types of fantasy novels. The research method used is descriptive qualitative with the data collection method, which is the first step in carrying out the observation method, followed by the reading and recording method. The source of the research data is in the form of data taken from the novel Bumi by Tere Liye. Furthermore, the data analysis method used is the flow model of analysis including data reduction, data presentation, and drawing conclusions. The results of the research conducted showed that the novel Bumi by Tere Liye has a complete structure and intertwining between intrinsic elements including theme, plot, characterization, setting, point of view, and language style that characterizes the author in the novel. The story in this novel is easy to understand because it uses an advanced or progressive plot by going through several stages, namely the initial stage (introduction), the conflict emergence stage, the complication stage, the climax stage, the resolution stage (problem solving), and the final stage. Characterization consisting of the protagonist and the antagonist. The setting used in this novel is also divided into a place setting, a time setting, and an atmosphere setting. The point of view used is the single first-person point of view as the main culprit. In addition, the type of Earth novels is included in the type of fantasy novels that are imaginative and imaginary of an author.